2008
DOI: 10.1111/j.1753-6405.2008.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb injuries in New Zealand Defence Force personnel: descriptive epidemiology

Abstract: Objective: To describe the epidemiology of lower limb injuries in the New Zealand Defence Force (NZDF). Method: Data from all NZDF lower limb injury claims from an 11‐month period were examined for type, site, and circumstances of injury. Both injury codes and narratives were analysed, allowing each injury event to be classified according to mechanism of injury, object involvement, and activity at the time of injury, as well as type and site. Results: The commonest lower limb musculoskeletal injuries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
(36 reference statements)
3
50
4
1
Order By: Relevance
“…In contrast to the findings of Davidson et al [40] who reported acute injuries as the most prevalent, our study found overuse the most commonly reported sub-classification of all military training MSKI as well as the most commonly observed across individual training regiments. Heagerty et al [2] investigating four years injury patterns found incidence of 76.9% (Guards) 75.2 (Line), 82.2% (Para) 80.3% (Gurkha) for overuse injuries when considered as a percentage of total MSKI.…”
Section: Type Of Injurycontrasting
confidence: 99%
“…In contrast to the findings of Davidson et al [40] who reported acute injuries as the most prevalent, our study found overuse the most commonly reported sub-classification of all military training MSKI as well as the most commonly observed across individual training regiments. Heagerty et al [2] investigating four years injury patterns found incidence of 76.9% (Guards) 75.2 (Line), 82.2% (Para) 80.3% (Gurkha) for overuse injuries when considered as a percentage of total MSKI.…”
Section: Type Of Injurycontrasting
confidence: 99%
“…[1][2][3][12][13][14] According to several studies, 1-3 the majority of ankle sprains documented within military personnel result from participation in organized and recreational sports, exercise, and physical training. Ankle sprains are not an isolated problem affecting US service members, as authors have documented a high rate of sportrelated, exercise-related, and physical training-related ankle sprains in British Army 3,13 and New Zealand Defense Force 2 populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to athletic injuries, the physical fitness and training-related requirements of military service increase soldiers' risk for musculoskeletal injury in general and injury to the lower extremity and ankle specifically. [1][2][3][4] Ankle sprains are one of the most common injuries sustained by members of the US Armed Services and are among the leading causes of sport-related and physical training-related hospitalizations in the military. 1 In general, ankle sprains are often undertreated and result in chronic pain, muscular weakness, and chronic instability.…”
mentioning
confidence: 99%
“…were excluded from our analysis as they were retrospective in design (19,(247)(248)(249)(250)(251). In studies and did not report specific data relating to sprain diagnosis.…”
Section: Discussionmentioning
confidence: 99%